Psychiatric comorbidity in treatment‐seeking substance use disorder patients with and without attention deficit hyperactivity disorder: results of the IASP study. (20th November 2013) - van, Katelijne; van de, Geurt; Koeter, Maarten W. J.; Allsop, Steve; Auriacombe, Marc; Barta, Csaba; Bu, Eli Torild H.; Burren, Yuliya; Carpentier, Pieter‐Jan; Carruthers, Susan; Casas, Miguel; Demetrovics, Zsolt; et al.
Abstract Aims To determine comorbidity patterns in treatment‐seeking substance use disorder (SUD) patients with and without adult attention deficit hyperactivity disorder (ADHD), with an emphasis on subgroups defined by ADHD subtype, taking into account differences related to gender and primary substance of abuse. Design Data were obtained from the cross‐sectional International ADHD in Substance use disorder Prevalence (IASP) study. Setting Forty‐seven centres of SUD treatment in 10 countries. Participants A total of 1205 treatment‐seeking SUD patients. Measurements Structured diagnostic assessments were used for all disorders: presence of ADHD was assessed with the Conners' Adult ADHD Diagnostic Interview for DSM‐IV (CAADID), the presence of antisocial personality disorder (ASPD), major depression (MD) and (hypo)manic episode (HME) was assessed with the Mini International Neuropsychiatric Interview‐Plus (MINI Plus), and the presence of borderline personality disorder (BPD) was assessed with the Structured Clinical Interview for DSM‐IV Axis II (SCID II). Findings The prevalence of DSM‐IV adult ADHD in this SUD sample was 13.9%. ASPD [odds ratio (OR) = 2.8, 95% confidence interval (CI) = 1.8–4.2], BPD (OR = 7.0, 95% CI = 3.1–15.6 for alcohol; OR = 3.4, 95% CI = 1.8–6.4 for drugs), MD in patients with alcohol as primary substance of abuse (OR = 4.1, 95% CI = 2.1–7.8) and HME (OR = 4.3, 95% CI = 2.1–8.7) were all more prevalent in ADHD+ compared with ADHD− patients (P < 0.001). These results also indicate increased levels of BPD and MD for alcohol compared with drugs as primary substance of abuse. Comorbidity patterns differed between ADHD subtypes with increased MD in the inattentive and combined subtype (P < 0.01), increased HME and ASPD in the hyperactive/impulsive (P < 0.01) and combined subtypes (P < 0.001) and increased BPD in all subtypes (P < 0.001) compared with SUD patients without ADHD. Seventy‐five per cent of ADHD patients had at least one additional comorbid disorder compared with 37% of SUD patients without ADHD. Conclusions Treatment‐seeking substance use disorder patients with attention deficit hyperactivity disorder are at a very high risk for additional externalizing disorders.